Determination of plastic properties of polycrystalline metallic materials by nanoindentation: Experiments and finite element simulations - Backes, Björn; Durst, Karsten; Göken, Mathias (Philosophical Magazine, 2006)
Nanoindentation experiments at low indentation depths are strongly influenced by micromechanical effects, such as the indentation size effect, pile-up or sink-in behaviour and crystal orientation of the investigated material. For an evaluation of load-displacement data and a reconstruction of stress-strain curves from nanoindentations, these micromechanical effects need to be considered. The influence of size effects on experiments were estimated by comparing the results of finite element simulation and experiments, using uniaxial stress-strain data of the indented material as input for the simulations. The experiments were performed on conventional and ultrafine-grained copper and brass, and the influence of the indentation size effect and pile-up formation is discussed in terms of microstructure. Applying a pile-up correction on Berkovich and cube-corner indentation data, a piecewise reconstruction of stress-strain curves from load-displacement data is possible with Tabor's concept of representative strain. A good approximation of the slope of the stress-strain curve from the indentation experiments is found for all materials down to an indentation depth of 800∈nm.
Created from Fastlane, Scopus look-up